Challenges and Benefits of Implementing Corporate Social Responsibility in MSMEs - Primadona, Ida Ayu Lidya; Rustiarini, Ni Wayan; Rismawati (Jurnal Inovasi Akuntansi (JIA), 2024)
The growth of the tourism sector in Bali has a positive impact on the development of MSMEs. MSME players also need to apply the concept of sustainability in their operational activities to support sustainable tourism, one of which is through Corporate Social Responsibility (CSR) practices. This research explores in depth the perceptions of MSME owners towards CSR practices and the benefits obtained from CSR practices. This study also analyzes the challenges faced by MSMEs in implementing CSR. This study is qualitative research using the interview method in data collection. Interviews were conducted with two food and beverage MSME owners in Denpasar City. The results show that MSME owners need to understand the concept of sustainability fully. However, they have awareness regarding the impact of business operations on stakeholders. However, small business owners have several challenges, such as limited resources and finances, so they have yet to focus on CSR activities. The findings imply the critical role of academics and government in assisting MSME owners in adopting the concept of sustainability in their business practices.